Research and development spillovers in ASEAN countries: the role of economic freedom - Nordin, Nurnaddia; Nordin, Nurhaiza; Zainudin, Norzalina (Faculty of Business, Economics and Accountancy, Universiti Malaysia Sabah, 2017)
The aim of this study is to examine the role economic freedom plays in R&D spillovers for the ASEAN-4 countries. The dynamic ordinary least square panel estimator (D-OLS) is employed using data from 1996 to 2015. There are three important conclusions that can be drawn from the reported results. First, foreign R&D is more important for productivity improvements than domestic R&D. Second, import is the main channel for foreign R&D spillovers. Third, economic freedom plays an important role in moderating both domestic and foreign R&D spillovers. Therefore, policymakers and governments should play an important role in promoting trade liberalization and other policies that enhance freedom of economic activities as both are expected to boost domestic productivity.